Qualitative research in business and management - Myers, Michael D. (Los Angeles, California : Sage, 2013)
This book is relevant for students in almost all of the business disciplines, including accounting, employment relations, finance, human resource management, information systems, international business, management, marketing, operations management, organization development and strategic management.
Part I : Introduction -- Part II : Fundamental concepts of research -- Part III : Qualitative research methods -- Part IV : Data collection techniques -- Part V : Analysis qualitative data -- Part VI : Writing up and publishing -- Part VII : Conclusion
Includes bibliographical references and index.
Keywords: MANAGEMENT -- RESEARCH